The clinical experience of croup at a tertiary care center in Jeddah, Western Saudi Arabia - Hazem Alhazmi (Saudi Journal of Emergency Medicine, 2023)
Background: Viral croup is an upper respiratory tract inflammation that commonly affects children. This paper reports the prevalence, clinical characteristics, outcomes, and management of patients with croup who presented to the emergency department of a tertiary care center in Jeddah, Saudi Arabia. Methods: A retrospective study was conducted using the hospital's electronic medical records of pediatric patients with croup aged 0–14 who presented to the emergency department between July 1, 2016, and December 30, 2022. A data collection sheet containing four sections–demographics, clinical manifestations, assessment, and management–was used. Statistical analysis was conducted using JMP statistical software version 15.2.0. Results: A total of 146 patients were included; 74 (50.68%) were under 2 years of age, and approximately half presented to the ER during autumn. Cough was the most common clinical manifestation, reported in 134 patients (91.78%). Regarding the Westley score, a mild grade was reported in 25 (58.14%) patients. Abnormal chest and neck radiographs were observed in 38 (60.32%) and 21 patients (65.63%). Regarding management, dexamethasone was administered to 131 (89.73 %) patients. Moreover, only 15 (10.27%) patients were hospitalized, and the rest were discharged from the emergency department. Conclusion: The study found that approximately half of the total emergency visits for croup cases occurred during autumn, with most patients under 2 years old. The most common clinical symptom noted in these patients was cough. Dexamethasone was administered to most patients; interestingly, most patients did not require hospitalization. [SJEMed 2023; 4(3.000): 157-161]